Magnetic porous silica gel as well as preparation method and application thereof

By preparing γ-Fe2O3 magnetic nanoparticles inside porous silica microspheres and covering silica on the surface, the problems of agglomeration of magnetic silica microspheres after magnetic field evacuation and magnetic particles falling off are solved, and magnetic porous silica gel with high magnetic responsiveness and stability are achieved, which is suitable for a variety of biotechnology and drug applications.

CN119657071APending Publication Date: 2025-03-21SUZHOU NANOMICRO TECH CO LTD

Patent Information

Application Number
CN202311215966.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-20
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing magnetic silicone microspheres still show particle agglomeration after the external magnetic field is evacuated, which hinders the repeated use of microspheres. They have poor particle size uniformity and low magnetic responsiveness, so that magnetic particles are prone to fall off.

Method used

Iron tetroxide is prepared in the pores inside the porous silica microspheres and calcined at high temperature to convert Fe3O4 nanoparticles into γ-Fe2O3 magnetic nanoparticles with higher magnetic responsiveness and chemical stability. At the same time, a layer of silica is coated on the pores and surface of the fully porous silica microspheres to prevent the magnetic nanoparticles from falling off.

Benefits of technology

It realizes the high magnetic responsiveness and chemical stability of magnetic porous silica gel, avoids the fall of magnetic particles, improves the stability and particle size uniformity of the material, and is suitable for catalysis, immobilization enzymes, nucleic acid extraction, cell screening and drug sustained release applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119657071A_ABST
    Figure CN119657071A_ABST
Patent Text Reader

Abstract

The invention provides magnetic porous silica gel as well as a preparation method and application thereof. The magnetic porous silica gel comprises a magnetic silica gel inner core and a silicon dioxide coating layer arranged on the surface of the magnetic silica gel inner core, the magnetic silica gel inner core comprises a porous silica gel carrier and # imgabs0 # magnetic nanoparticles loaded on internal pore channels of the porous silica gel carrier. Ferroferric oxide is prepared in pores inside the porous silica gel microspheres through a simple method, and Fe3O4 nanoparticles are converted into # imgabs1 # magnetic nanoparticles with higher magnetic responsiveness and chemical stability through high-temperature calcination, so that the problem of magnetism weakening is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of silica gel preparation, and relates to magnetic porous silica gel and a preparation method and application thereof. Background Art

[0002] Magnetic porous silica microspheres have the advantages of large surface area, easy surface functionalization, good biocompatibility, easy separation under a magnetic field, and easy automation of separation operations. They are widely used in catalysis, immobilized enzymes, nucleic acid extraction, cell screening, and drug controlled release. They have become a research hotspot in many fields such as material chemistry, separation science, biotechnology, and drug development.

[0003] At present, magnetic silica mesoporous microspheres are mainly prepared by impregnation, coating and template methods. The obtained products have high residual magnetism. After the external magnetic field is withdrawn, the particles still show agglomeration phenomenon, which hinders the repeated use of the microspheres to a certain extent. Therefore, it is of great scientific significance and practical value to develop a preparation method for silica mesoporous microspheres with high magnetic responsiveness and superparamagnetism, and implement surface functionalization of microspheres to further broaden the application field of magnetic materials.

[0004] CN113559830A discloses a magnetic porous spherical silica microsphere and a preparation method thereof, but the method requires the pre-preparation of Fe3O4 magnetic fluid and silica sol, and also requires the surface of the Fe3O4 nanoparticles to be covered with a layer of silicon dioxide, so the preparation process is relatively complicated and the cost is high. In addition, the prepared magnetic porous spherical silica microsphere has a particle size distribution of 20-50 μm, poor monodispersity, and uneven particle size.

[0005] CN107175064A discloses a magnetic microsphere silica gel and a preparation method thereof, but this method also requires the pre-preparation of 10-25nm Fe3O4 magnetic fluid, and the pore expansion by alkaline heat treatment is required on the basis of the preparation of small-pore silica gel. The process is relatively complicated and the particle size is difficult to accurately control.

[0006] CN112604657A discloses a vancomycin magnetic silica microsphere stationary phase and its preparation method and application. However, this method is to fill the pre-prepared Fe3O4 magnetic fluid into the pores of the silica microspheres. The filling process cannot be controlled, which easily leads to a large number of Fe3O4 nanoparticles sticking to the surface of the silica microspheres. There is a risk of falling off during use, causing inevitable losses to samples and subsequent tests.

[0007] The magnetic microspheres prepared by the method described in the above scheme have poor uniformity in particle size and low magnetic responsiveness, and the magnetic particles are easy to fall off, which can easily cause losses to varying degrees. Therefore, there is an urgent need to develop a preparation method for magnetic porous silica gel with uniform particle size, high magnetic responsiveness, no risk of magnetic particle falling off, high specific surface area, simple steps, high efficiency, simple equipment, and easy industrial production. Summary of the invention

[0008] The purpose of the present invention is to provide a magnetic porous silica gel and a preparation method and application thereof. The present invention prepares ferroferric oxide in the pores inside the porous silica gel microspheres by a simple method, and converts Fe3O4 nanoparticles into γ-Fe2O3 magnetic nanoparticles with higher magnetic responsiveness and chemical stability by high-temperature calcination, thereby solving the problem of weakened magnetism. The method has mild preparation conditions, simple operation, controllable process, and is easy to mass-produce. In addition, the method has strong versatility and can be used to prepare magnetic silica gel microspheres with different particle sizes.

[0009] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a magnetic porous silica gel, comprising a magnetic silica gel core and a silica coating layer arranged on the surface of the magnetic silica gel core, wherein the magnetic silica gel core comprises a porous silica gel carrier and γ-Fe2O3 magnetic nanoparticles loaded on the internal pores of the porous silica gel carrier.

[0011] The magnetic particles in the magnetic porous silica gel of the present invention are γ-Fe2O3 magnetic nanoparticles, which improve the magnetic responsiveness of the material while making the magnetic fully porous silica gel have good suspension, high specific surface area and high porosity. The magnetic particles are loaded into the internal pores of the magnetic fully porous silica gel, and there are no magnetic particles on the surface. In addition, a layer of silicon dioxide is coated on the pores and surface of the fully porous silica gel, which can solve the problem of magnetic particles falling off during the use of the magnetic silica gel microspheres.

[0012] Preferably, the particle size of the porous silica gel carrier is 3 to 50 μm, for example, 3 μm, 5 μm, 10 μm, 20 μm or 50 μm.

[0013] Preferably, the pore size inside the porous silica gel carrier is 5 to 20 nm, for example, 5 nm, 8 nm, 10 nm, 15 nm or 20 nm.

[0014] Preferably, the specific surface area of ​​the magnetic porous silica gel is 200 to 800 m 2 / g, for example: 200m 2 / g, 400m 2 / g、500m 2 / g, 600m 2 / g or 800m 2 / g, etc.

[0015] Preferably, the magnetic porous silica gel has a magnetization intensity of 8 to 40 emu / g, for example, 8 emu / g, 10 emu / g, 20 emu / g, 30 emu / g or 40 emu / g.

[0016] In a second aspect, the present invention provides a method for preparing the magnetic porous silica gel as described in the first aspect, the preparation method comprising the following steps:

[0017] (1) mixing an iron salt solution and porous silica microspheres, and immersing them in ultrasound to obtain porous silica microspheres loaded with iron salts;

[0018] (2) calcining the porous silica gel microspheres loaded with iron salt to obtain a calcined material;

[0019] (3) calcining the first-fired material in two steps to obtain a second-fired material;

[0020] (4) The di-sintered material is mixed with hydrofluoric acid, and a silicon source is added after a one-step reaction, and the magnetic porous silica gel is obtained through a two-step reaction.

[0021] The present invention first uses an impregnation method to load iron salts on the pores inside the porous silica microspheres, and then converts the iron salts into Fe3O4 magnetic particles through a one-step calcination. Since the Fe3O4 nanoparticles will be partially oxidized when placed in the air for a long time, the magnetism will be weakened. The present invention can convert the Fe3O4 nanoparticles into γ-Fe2O3 magnetic nanoparticles with higher magnetic responsiveness and chemical stability through a two-step calcination, thereby solving the problem of weakened magnetism. The magnetic particles are not easy to fall off in the pores inside the porous silica gel. The present application further prevents the magnetic nanoparticles from falling off from the inside by coating the pores and surfaces of the porous silica microspheres with a layer of silicon dioxide (SiO2), thereby further improving the stability of the material.

[0022] Preferably, the iron salt solution in step (1) comprises ferric nitrate solution.

[0023] Preferably, the concentration of the iron salt solution is 200-300 g / L, for example, 200 g / L, 220 g / L, 250 g / L, 280 g / L or 300 g / L.

[0024] Preferably, the solvent of the iron salt solution includes any one of anhydrous ethanol, methanol or water, or a combination of at least two of them.

[0025] Preferably, the particle size of the porous silica microspheres is 3 to 50 μm, for example, 3 μm, 5 μm, 10 μm, 30 μm or 50 μm.

[0026] Preferably, the pore size of the porous silica microspheres is 8-12 nm, for example, 8 nm, 9 nm, 10 nm, 11 nm or 12 nm.

[0027] Preferably, the ultrasonic immersion time is 20 to 30 hours, for example, 20 hours, 23 hours, 25 hours, 28 hours or 30 hours.

[0028] Preferably, the porous silica gel microspheres loaded with iron salt are repeatedly ultrasonically immersed 2 to 3 times.

[0029] The present invention can adjust the magnetic properties of the magnetic porous silica gel by controlling the number of times the porous silica gel microspheres are immersed in the iron salt solution.

[0030] Preferably, the acoustic soaking in step (1) is followed by filtration, washing and drying.

[0031] Preferably, the washing detergent comprises anhydrous ethanol.

[0032] Preferably, the washing is performed 2 to 4 times, for example 2, 3 or 4 times.

[0033] The invention can wash away the iron salt on the surface of the porous silica gel microspheres through multiple washing treatments, so that the iron salt is evenly distributed in the internal pores of the porous microspheres, thereby improving the stability of the material.

[0034] Preferably, the drying treatment temperature is 40-60°C, for example, 40°C, 45°C, 50°C, 55°C or 60°C.

[0035] Preferably, the drying time is 5 to 8 hours, for example, 5 hours, 5.5 hours, 6 hours, 7 hours or 8 hours.

[0036] Preferably, the heating rate of the one-step calcination treatment in step (2) is 4 to 6°C / min, for example, 4°C / min, 4.5°C / min, 5°C / min, 5.5°C / min or 6°C / min.

[0037] Preferably, the temperature of the one-step calcination treatment is 500-700°C, for example, 500°C, 550°C, 600°C, 650°C or 700°C.

[0038] Preferably, the atmosphere of the one-step calcination treatment comprises nitrogen.

[0039] In the one-step calcination process of the present invention, in a nitrogen atmosphere, a small amount of carbon contained in the porous silica gel can reduce part of the trivalent iron to divalent iron, thereby generating magnetic ferrosoferric oxide.

[0040] Preferably, the one-step calcination treatment lasts for 3 to 5 hours, for example, 3 hours, 3.5 hours, 4 hours, 4.5 hours or 5 hours.

[0041] Preferably, the one-step calcination treatment is followed by a cooling treatment.

[0042] Preferably, the cooling temperature is 20-30°C, for example, 20°C, 22°C, 25°C, 28°C or 30°C.

[0043] Preferably, the heating rate of the two-step calcination treatment in step (3) is 4 to 6°C / min, for example, 4°C / min, 4.5°C / min, 5°C / min, 5.5°C / min or 6°C / min.

[0044] Preferably, the temperature of the two-step calcination treatment is 500-700°C, for example, 500°C, 550°C, 600°C, 650°C or 700°C.

[0045] Preferably, the atmosphere of the two-step calcination treatment includes air.

[0046] The two-step calcination treatment of the present invention is carried out in an air atmosphere, the divalent iron in the ferroferric oxide is oxidized, and the ferroferric oxide is converted into γ-Fe2O3 with stronger magnetism and higher chemical stability.

[0047] Preferably, the two-step calcination treatment lasts for 3 to 5 hours, for example, 3 hours, 3.5 hours, 4 hours, 4.5 hours or 5 hours.

[0048] Preferably, the two-step calcination treatment is followed by a cooling treatment.

[0049] Preferably, the cooling temperature is 20-30°C, for example, 20°C, 22°C, 25°C, 28°C or 30°C.

[0050] Preferably, the concentration of the hydrofluoric acid in step (4) is 0.3-0.5wt%, for example: 0.3wt%, 0.35wt%, 0.4wt%, 0.45wt% or 0.5wt%, etc.

[0051] Preferably, the mass ratio of the di-sintered material to hydrofluoric acid is 1:(5-15), for example: 1:5, 1:8, 1:10, 1:12 or 1:15, etc.

[0052] Preferably, ultrasonic stirring is performed during the one-step reaction.

[0053] Preferably, the ultrasonic stirring time is 1 to 3 hours, for example: 1 hour, 1.5 hours, 2 hours, 2.5 hours or 3 hours.

[0054] Preferably, the silicon source in step (4) comprises tetraethyl silicate.

[0055] Preferably, the mass ratio of the silicon source to the di-sintered material is 1:(5-15), for example: 1:5, 1:8, 1:10, 1:12 or 1:15, etc.

[0056] Preferably, the temperature of the two-step reaction is 40-60°C, for example, 40°C, 45°C, 50°C, 55°C or 60°C.

[0057] Preferably, the two-step reaction time is 20 to 30 h, for example, 20 h, 23 h, 25 h, 28 h or 30 h.

[0058] Preferably, the two-step reaction in step (4) is followed by washing and drying.

[0059] Preferably, the washing detergent comprises anhydrous ethanol.

[0060] Preferably, the washing is performed 2 to 4 times, for example 2, 3 or 4 times.

[0061] Preferably, the drying temperature is 40-60°C, for example, 40°C, 45°C, 50°C, 55°C or 60°C.

[0062] Preferably, the drying time is 5 to 8 hours, for example, 5 hours, 5.5 hours, 6 hours, 7 hours or 8 hours.

[0063] In a third aspect, the present invention provides an application of the magnetic porous silica gel as described in the first aspect, wherein the magnetic porous silica gel is used for catalysis, enzyme immobilization, nucleic acid extraction, cell screening or drug sustained release.

[0064] Compared with the prior art, the present invention has the following beneficial effects:

[0065] (1) The present invention prepares ferroferric oxide in the pores inside porous silica microspheres by a simple method, and converts Fe3O4 nanoparticles into γ-Fe2O3 magnetic nanoparticles with higher magnetic responsiveness and chemical stability by high-temperature calcination, thereby solving the problem of weakened magnetism. The method has mild preparation conditions, simple operation, controllable process, and is easy to mass-produce. In addition, the method has strong versatility and can be used to prepare magnetic silica microspheres with different particle sizes.

[0066] (2) The magnetic fully porous silica gel prepared by the present invention has good suspension, rapid magnetic responsiveness, high specific surface area and high porosity. The magnetic particles are loaded into the internal pores of the magnetic fully porous silica gel, and there are no magnetic particles on the surface. In addition, a layer of silicon dioxide is coated on the pores and surface of the fully porous silica gel, which can solve the problem of magnetic particles falling off during the use of magnetic silica gel microspheres. BRIEF DESCRIPTION OF THE DRAWINGS

[0067] Figure 1This is a flow chart of the preparation process of the magnetic porous silica gel described in Example 1 of the present invention.

[0068] Figure 2 It is a schematic diagram of the synthesis of the magnetic porous silica gel described in Example 1 of the present invention.

[0069] Figure 3 This is a SEM image of the magnetic porous silica gel described in Example 1 of the present invention.

[0070] Figure 4 This is a SEM image of the magnetic porous silica gel described in Example 2 of the present invention.

[0071] Figure 5 This is a SEM image of the magnetic porous silica gel described in Example 3 of the present invention.

[0072] Figure 6 This is a SEM image of the magnetic porous silica gel described in Example 4 of the present invention.

[0073] Figure 7 This is a SEM image of the magnetic porous silica gel described in Example 5 of the present invention. DETAILED DESCRIPTION

[0074] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0075] The porous silica microspheres used in the examples and comparative examples of the present invention were purchased from Suzhou Nanovita Technology Co., Ltd.

[0076] Example 1

[0077] This embodiment provides a magnetic porous silica gel, and the preparation process flow chart of the magnetic porous silica gel is as follows: Figure 1 As shown, the structural formula of the magnetic porous silica gel preparation method is as follows Figure 2 As shown, the preparation method of the magnetic porous silica gel is as follows:

[0078] (1) 1.8 L of 240 g / L ferric nitrate solution was mixed with 100 g of porous silica microspheres with a particle size of 3 μm and a pore size of 10 nm, stirred evenly and ultrasonically soaked at 25° C. for 24 h, filtered and washed three times with anhydrous ethanol, and dried at 50° C. in a vacuum for 6 h to obtain silica microspheres loaded with ferric nitrate (denoted as UniH-3-100-1);

[0079] (2) placing the dried UniH-3-100-1 microspheres in a vacuum tube furnace, heating the temperature to 600°C at a rate of 5°C / min in a nitrogen atmosphere of the tube furnace, maintaining the temperature at 600°C for 4 hours, and cooling the temperature to room temperature (25°C) to obtain a sintered material;

[0080] (3) placing the first-fired material in an empty tube furnace, heating it to 600° C. at a rate of 5° C. / min in an air atmosphere of the tube furnace, maintaining it at 600° C. for 4 h, and then cooling it to room temperature (25° C.) to obtain a second-fired material;

[0081] (4) 100 g of the di-sintered material was dispersed in 1000 g of hydrofluoric acid with a concentration of 0.4 wt %, and 10 g of tetraethyl silicate was added under ultrasonic stirring for 2 h. The mixture was stirred at 50 ° C for 24 h, filtered and washed three times with anhydrous ethanol, and dried in a vacuum at 50 ° C for 6 h to obtain the magnetic porous silica gel.

[0082] The SEM image of the magnetic porous silica gel is as follows: Figure 3 As shown. Figure 3 It can be seen that the surface of the magnetic porous silica microspheres is smooth and no magnetic particles grow on the surface.

[0083] The performance of the magnetic porous silica microspheres was tested. The sample was reddish brown in color, with a particle size of 3 μm, good suspension, general magnetic responsiveness, and a magnetization intensity of 8 emu / g. 0.1 g of magnetic microspheres were dispersed in a 10 mL centrifuge tube filled with ethanol. Under the action of a magnet, the sample could be clarified within 30 seconds. The N2 adsorption-desorption isotherm showed that the specific surface area was 606 m 2 / g, pore size is 1.4cm 3 / g, average pore size 9.8nm.

[0084] Example 2

[0085] This embodiment provides a magnetic porous silica gel, and the preparation method of the magnetic porous silica gel is as follows:

[0086] (1) 2 L of 200 g / L ferric nitrate solution was mixed with 100 g of porous silica microspheres with a particle size of 3 μm and a pore size of 10 nm, stirred evenly and ultrasonically soaked at 25° C. for 20 h, filtered and washed twice with anhydrous ethanol, and dried at 50° C. in a vacuum for 6 h to obtain silica microspheres loaded with ferric nitrate, and the silica microspheres loaded with ferric nitrate were ultrasonically soaked in the ferric nitrate solution again, and the above steps were repeated to obtain silica microspheres loaded with secondary ferric nitrate (denoted as UniH-3-100-2);

[0087] (2) placing the dried UniH-3-100-2 microspheres in a vacuum tube furnace, heating the temperature to 500°C at a rate of 4°C / min in a nitrogen atmosphere of the tube furnace, maintaining the temperature at 500°C for 5 h, and cooling the temperature to room temperature (25°C) to obtain a sintered material;

[0088] (3) placing the first-fired material in an empty tube furnace, heating it to 500° C. at a rate of 4° C. / min in an air atmosphere of the tube furnace, maintaining it at 500° C. for 5 h, and then cooling it to room temperature (25° C.) to obtain a second-fired material;

[0089] (4) 100 g of the di-sintered material was dispersed in 500 g of hydrofluoric acid with a concentration of 0.3 wt %, and 5 g of tetraethyl silicate was added under ultrasonic stirring for 2 h. The mixture was stirred at 40° C. for 30 h, filtered and washed twice with anhydrous ethanol, and dried in a vacuum at 40° C. for 8 h to obtain the magnetic porous silica gel.

[0090] The SEM image of the magnetic porous silica gel is as follows: Figure 4 As shown. Figure 4 It can be seen that no magnetic particles grow on the surface of the magnetic porous silica microspheres.

[0091] The performance of the magnetic porous silica microspheres was tested. The sample was reddish brown in color, had good suspension properties, and had a further enhanced magnetic responsiveness. The magnetization intensity was 18emu / g. 0.1g of magnetic microspheres were dispersed in a 10mL centrifuge tube filled with ethanol. Under the action of the magnet, the sample could be clarified within 15s. The specific surface area was 455m2 according to the N2 adsorption-desorption isotherm. 2 / g, pore size is 1.1cm 3 / g, average pore size 9.5nm.

[0092] Example 3

[0093] This embodiment provides a magnetic porous silica gel, and the preparation method of the magnetic porous silica gel is as follows:

[0094] (1) 1.5 L of 300 g / L ferric nitrate solution was mixed with 100 g of porous silica microspheres with a particle size of 3 μm and a pore size of 10 nm, stirred evenly and ultrasonically soaked at 25° C. for 30 h, filtered and washed four times with anhydrous ethanol, and dried at 50° C. in a vacuum for 6 h to obtain silica microspheres loaded with ferric nitrate, and the silica microspheres loaded with ferric nitrate were ultrasonically soaked in the ferric nitrate solution again, and the above steps were repeated twice to obtain silica microspheres loaded with ferric nitrate for three times (denoted as UniH-3-100-3);

[0095] (2) placing the dried UniH-3-100-3 microspheres in a vacuum tube furnace, heating the temperature to 700°C at a rate of 6°C / min in a nitrogen atmosphere of the tube furnace, maintaining the temperature at 700°C for 3 h, and cooling the temperature to room temperature (25°C) to obtain a sintered material;

[0096] (3) placing the first-fired material in an empty tube furnace, heating it to 700° C. at a rate of 6° C. / min in an air atmosphere of the tube furnace, maintaining it at 700° C. for 3 h, and then cooling it to room temperature (25° C.) to obtain a second-fired material;

[0097] (4) 100 g of the di-sintered material was dispersed in 1500 g of hydrofluoric acid with a concentration of 0.3 wt %, and 15 g of tetraethyl silicate was added under ultrasonic stirring for 2 h. The mixture was stirred at 60 ° C for 20 h, filtered and washed four times with anhydrous ethanol, and dried in a vacuum at 60 ° C for 5 h to obtain the magnetic porous silica gel.

[0098] The SEM image of the magnetic porous silica gel is as follows: Figure 5 As shown. Figure 5 It can be seen that no magnetic particles grow on the surface of the magnetic porous silica microspheres.

[0099] The performance of the magnetic porous silica microspheres was tested. The sample was reddish brown in color, had good suspension properties, excellent magnetic responsiveness, and a magnetization intensity of 27emu / g. 0.1g of magnetic microspheres were dispersed in a 10mL centrifuge tube filled with ethanol. Under the action of a magnet, the sample could be clarified within 5s. The specific surface area was 289m2 according to the N2 adsorption-desorption isotherm. 2 / g, pore size is 0.6cm 3 / g, average pore size 8.7nm.

[0100] Example 4

[0101] The only difference between this embodiment and embodiment 3 is that the particle size of the porous silica microspheres is 5 μm, and the other conditions and parameters are exactly the same as those of embodiment 3.

[0102] The SEM image of the obtained magnetic porous silica gel is as follows: Figure 6 As shown by Figure 6 It can be seen that the surface of the magnetic porous silica microspheres is smooth and no magnetic particles grow on the surface.

[0103] The performance of the magnetic porous silica gel microspheres was tested. The sample was reddish brown in color, with a particle size of 5 μm, uniform particle size, good suspension properties, good magnetic responsiveness, and a magnetization intensity of 25 emu / g.

[0104] Example 5

[0105] The only difference between this embodiment and embodiment 3 is that the particle size of the porous silica gel microspheres is 30 μm, and the other conditions and parameters are exactly the same as those of embodiment 3. The SEM image of the obtained magnetic porous silica gel is as follows: Figure 7 shown.

[0106] The SEM image of the obtained magnetic porous silica gel is as follows: Figure 7 As shown by Figure 7 It can be seen that the surface of the magnetic porous silica microspheres is smooth and no magnetic particles grow on the surface.

[0107] The performance of the magnetic porous silica microspheres was tested. The sample was reddish brown in color, with a particle size of 30 μm, uniform particle size, excellent magnetic responsiveness, and a magnetization intensity of 30 emu / g.

[0108] Example 6

[0109] The only difference between this embodiment and embodiment 3 is that the particle size of the porous silica microspheres is 50 μm, and the other conditions and parameters are exactly the same as those in embodiment 3.

[0110] The performance of the magnetic porous silica microspheres was tested. The sample was reddish brown in color, with a particle size of 50 μm, uniform particle size, excellent magnetic responsiveness, and a magnetization intensity of 31 emu / g.

[0111] Comparative Example 1

[0112] The only difference between this comparative example and Example 1 is that the two-step calcination treatment is not performed, and the other conditions and parameters are exactly the same as those in Example 1.

[0113] The obtained magnetic porous silica microspheres were tested for performance. The sample was black in color, with a particle size of 3 μm, uniform in particle size, and insufficient in magnetic responsiveness. 0.1 g of magnetic microspheres were dispersed in a centrifuge tube filled with 10 mL of ethanol. Under the action of a magnet, the sample could not be completely absorbed and clarified within 60 seconds. Comparative Example 1 shows that the present invention can enhance magnetic responsiveness by converting Fe3O4 nanoparticles into γ-Fe2O3 magnetic nanoparticles through two-step calcination.

[0114] It can be seen from the above embodiments and comparative examples that the magnetic fully porous silica gel prepared by the method of the present invention can accurately adjust the magnetic strength by adjusting the number of times of immersion in ferric nitrate solution. The prepared magnetic fully porous silica gel has good suspension, fast magnetic responsiveness, high specific surface area, and high porosity. In addition, the magnetic particles are loaded into the internal pores of the magnetic fully porous silica gel, and there are no magnetic particles on the surface. The present invention converts Fe3O4 nanoparticles into γ-Fe2O3 magnetic nanoparticles in the air, which can enhance magnetic responsiveness and stability.

[0115] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A magnetic porous silica gel, characterized in that: The magnetic porous silica gel comprises a magnetic silica gel core and a silicon dioxide coating layer arranged on the surface of the magnetic silica gel core. The magnetic silica gel core comprises a porous silica gel carrier and γ-Fe2O3 magnetic nanoparticles loaded on the internal pores of the porous silica gel carrier.

2. The magnetic porous silica gel according to claim 1, characterized in that: The particle size of the porous silica gel carrier is 3 to 50 μm; Preferably, the pore size inside the porous silica gel carrier is 5 to 20 nm.

3. The magnetic porous silica gel according to claim 1 or 2, characterized in that: The specific surface area of ​​the magnetic porous silica gel is 200 to 800 m 2 / g; Preferably, the magnetic porous silica gel has a magnetization intensity of 8 to 40 emu / g.

4. A method for preparing the magnetic porous silica gel according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) mixing an iron salt solution and porous silica microspheres, and immersing them in ultrasound to obtain porous silica microspheres loaded with iron salts; (2) calcining the porous silica gel microspheres loaded with iron salt to obtain a calcined material; (3) calcining the first-fired material in two steps to obtain a second-fired material; (4) The di-sintered material is mixed with hydrofluoric acid, and a silicon source is added after a one-step reaction, and the magnetic porous silica gel is obtained through a two-step reaction.

5. The preparation method according to claim 4, characterized in that: The iron salt solution in step (1) comprises ferric nitrate solution; Preferably, the concentration of the iron salt solution is 200-300 g / L; Preferably, the solvent of the iron salt solution includes any one of anhydrous ethanol, methanol or water, or a combination of at least two thereof; Preferably, the particle size of the porous silica microspheres is 3 to 50 μm; Preferably, the pore size of the porous silica microspheres is 8 to 12 nm; Preferably, the ultrasonic immersion time is 20 to 30 hours; Preferably, the ultrasonic soaking is followed by filtration, washing and drying; Preferably, the washing detergent comprises anhydrous ethanol; Preferably, the washing is performed 2 to 4 times; Preferably, the drying temperature is 40-60°C; Preferably, the drying time is 5 to 8 hours; Preferably, the porous silica gel microspheres loaded with iron salt are repeatedly ultrasonically immersed 2 to 3 times.

6. The preparation method according to claim 4 or 5, characterized in that: The heating rate of the one-step calcination treatment in step (2) is 4 to 6°C / min; Preferably, the temperature of the one-step calcination treatment is 500-700°C; Preferably, the atmosphere of the one-step calcination treatment comprises nitrogen; Preferably, the one-step calcination treatment time is 3 to 5 hours; Preferably, the one-step calcination treatment is followed by a cooling treatment; Preferably, the cooling temperature is 20-30°C.

7. The preparation method according to any one of claims 4 to 6, characterized in that: The heating rate of the two-step calcination treatment in step (3) is 4 to 6°C / min; Preferably, the temperature of the two-step calcination treatment is 500-700°C; Preferably, the atmosphere of the two-step calcination treatment includes air; Preferably, the two-step calcination treatment time is 3 to 5 hours; Preferably, the two-step calcination treatment is followed by a cooling treatment; Preferably, the cooling temperature is 20-30°C.

8. The preparation method according to any one of claims 4 to 7, characterized in that: The concentration of the hydrofluoric acid in step (4) is 0.3-0.5 wt %; Preferably, the mass ratio of the di-sintered material to the hydrofluoric acid is 1:(5-15); Preferably, ultrasonic stirring is performed during the one-step reaction; Preferably, the ultrasonic stirring time is 1 to 3 hours; Preferably, the silicon source comprises tetraethyl silicate; Preferably, the mass ratio of the silicon source to the di-sintered material is 1:(5-15); Preferably, the temperature of the two-step reaction is 40-60°C; Preferably, the two-step reaction time is 20 to 30 hours.

9. The preparation method according to any one of claims 4 to 8, characterized in that: After the two-step reaction in step (4), washing and drying are performed; Preferably, the washing detergent comprises anhydrous ethanol; Preferably, the washing is performed 2 to 4 times; Preferably, the drying temperature is 40-60°C; Preferably, the drying time is 5 to 8 hours.

10. An application of the magnetic porous silica gel according to any one of claims 1 to 3, characterized in that: The magnetic porous silica gel is used for catalysis, enzyme immobilization, nucleic acid extraction, cell screening or drug sustained release.

Citation Information

Patent Citations

  • Magnetic microsphere silica gel and preparation method thereof

    CN107175064A

  • Vancomycin magnetic silica gel microsphere stationary phase as well as preparation method and application thereof

    CN112604657A

  • Magnetic porous spherical silica gel microsphere and preparation method thereof

    CN113559830A

Cited By

  • Catalyst for preparing coal modified pitch at low temperature and preparation method thereof

    CN121623815A